The effect of converters numbers on the blocking probability parameter of the WSW2 switching fabric - Abdulkareem, Aws (2019)
In the current study, the Wavelength-Space-Wavelength (W-S-W) switching fabrics are considered for performance evaluation purpose. WSW2 architecture, which is derived from Clos switching fabrics, is made up of three phases. In the first and third stages, the converting switches of the bandwidth-variable waveband are contained, while the central phase is made up of bandwidth-variable waveband selective space switches. This design is capable of shifting the optical wavelength of connections within the first and last stages, while the second stage merely forwards the connections in the space domain. The switching fabric is capable of switching the switch m-slot connections occupying the m adjacent slots, 1 ≤ m ≤ mmax. Recently, few papers, which have been published in this area, investigated the strict-sense (SSNB) and wide-sense (WSNB) non-blocking conditions of these kind of switching fabrics. A large number of center stage switches and spectrum converters are required by SSNB and WSNB switching fabrics. In this research, an evaluation of the blocking switching fabrics has been done with the aim of identifying the optimal number of spectrum converters and/or center stage switches. The performance evaluation has been carried out using simulation that is implemented in C++ programming language. Simulation results have provided insights on the relationship between the number of converters and blocking probability of the mentioned switching.